Pengaruh Perceived Trustworthiness Of EWOM, Percieved Value Dan Customer Engagement Terhadap Purchase Intention - Bambang Setiyo Pambudi; Sri Hartini; Sony Kusumasondjaja (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2022)
Consumer attitudes towards eWOM on social media are the main information source in determining consumer attitudes. The increasing amount of information on social media makes it difficult for consumers to find trust in eWOM, especially in health products. A higher level of trust is needed for health products (Shah et al., 2019). This research is a development of Mehrabian, Russell's S-O-R (Stimulus, Organims, Response) Theory in 1974. The model shows that the form of response is a back reaction from individuals when receiving stimuli. The focus of the research is a causal influence in the eWOM model to build trust, increase the benefits and value of a product, and establish consumer involvement so that there is a change in behavior attitude on purchase intention. There are three elements in the S-O-R communication model: 1. Stimulus consists of Perceived Trustworthiness of eWOM and Perceived Value 2. Organizations, namely Customer engagement, and 3. Response, namely Purchase intention. The research was conducted on social media users Facebook or Instagram Tik Tok. Sample with purposive sampling, characteristics.